OPTIMALISASI PROYEK PEMBANGUNAN LAPANGAN PENUMPUKAN EKS DELTA DI PELABUHAN TANJUNG PRIOK OLEH PT. ARYA PERMATA NUSA INDAH DENGAN MENGGUNAKAN METODE CPM, PERT DAN CRASHING - Robi Anggara, (2022)
In a construction project there are three important aspects that must be considered, such as time, cost, and quality. Projects generally have a deadline, it means the projects must be completed before or on time so there are no delays. In this research, the case study used for the analysis of the acceleration of the project time is the construction project of the ex-delta stacking field in Tanjung Priok Port by PT. Arya Permata Nusa Indah. This development process takes 185 days. the ex-delta stacking field construction project was delayed for 2 weeks and an acceleration was needed to reduce delays. The purpose of this research is to effectively accelerate the project completion time in terms of cost and analyze the effectiveness of the shortened time using the CPM, PERT and Crashing overtimes methods. So that it can be seen the most effective and efficient acceleration of project duration and the use of costs that do not exceed the budget of this project. The results of this study there are 19 critical path activities and where in these activities crashing is carried out with alternatives of 1 hour, 2 hours, 3 hours adding overtime hours. From these alternatives, the most optimal acceleration in the ex-delta stacking field construction project is the addition of 1 hour of overtime with an acceleration of 166 days from 185 days at a cost of Rp. 11,199,974,548 from the normal cost of Rp. 11,047,559,134.